Threat Intelligence-Driven Cybersecurity for IoT Ecosystems: A Raspberry Pi-based Analysis of Smart Home Security - Addison, Samuel (My University, 2024)
Households have become more automated due to the spread of smart home technology, offering increased convenience. However, with this rise in smart home adoption comes an elevated risk of cyber threats, necessitating stronger security measures. While smart home security has received attention, few studies have explored the integration of threat intelligence to enhance cybersecurity in this domain. This study addresses that gap by examining how threat intelligence can improve smart home cybersecurity. Using Raspberry Pi as a representative smart home device, the research evaluates various types of cyber attacks, including brute-force and denial-of-service attacks, and assesses the effectiveness of threat intelligence platforms in mitigating these threats. The findings demonstrate that integrating threat intelligence significantly enhances threat detection and response, outperforming traditional firewall-based systems by providing real-time updates on indicators of compromise (IoCs). The system achieved a detection and prevention rate of 99.9\%, ensuring accurate identification and prevention of threats. This proactive approach not only improves the security posture in smart homes but also highlights how such methods can preemptively mitigate emerging cyber threats. Finally, the study provides suggestions for future research and discusses practical applications to advance smart home cybersecurity through threat intelligence solutions.
Keywords: Smart Home Security, Cybersecurity, Threat Intelligence, Indicators of Compromise (IoCs), Real-Time Updates, Internet of Things (IoT), IoT Ecosystem, Firewalls, Intrusion Detection Systems (IDS), Intrusion Prevention Systems (IPS), Open-source Secuirty Tools, Threat Intelligence Tools, Suricata IDS/IPS, Raspberry Pi, Cyber Threat Detection, Proactive Cybersecurity Measures, Denial-of-Service (DoS) Attacks, Brute-Force Attacks, Security Enhancement, MISP (Malware Information Sharing Platform)